Super spellers starter sets - Weakland, Mark (Stenhouse Publishers, 2019)
"This project is a companion teacher resource to Mark's original book, Super Spellers - it includes a brief overview of spelling instruction along with 21 lesson sets, divided into two grade bands (1-3 and 3-5) as well as chapters on general strategy lessons and independent center/workstation ideas"--